Prevalence of Hypertension in Neonates: A study in two Tertiary Care Hospitals of Bangladesh - Hasan, A N M Saiful; Khan, Md Anwar Hossain; Alom, Kabir; Akhtar, Shahnaz; Pervez, Abu Faisal Md; Pervez, Abu Faisal Md; Miah, Md Abu Sayed; Patowary, Md Asaduzzaman; Begum, Rokeya (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Hypertension is a condition which is usually not common in neonates. If hypertension can be detected early in neonates it is possible to decrease morbidity and mortality in future by taking appropriate measures. This cross sectional study was carried out in two tertiary care hospitals to find out the prevalence of hypertension in neonates. Study period was from July, 2017 to June 2018. To determine the prevalence of neonatal hypertension, 600 neonates were included. Blood pressure was measured by using neonatal cuff; on three occasions at same visit at least 5 minutes interval while neonates were quiet and awake. Out of the 600 neonates only two had hypertension (0.33%). Both hypertensive neonates were male and detected in Neonatal Intensive Care Unit (NICU). The prevalence of hypertension in term and preterm neonates were 0.57% and 0.23% respectively. Paired samples test of blood pressure of neonates showed significant value with birth weight in kg and gestational age in weeks. Linear regression showed increase blood pressure with increasing gestational age of neonates. In this study 95% of neonates had blood pressure at or lower than reference value. It can be concluded from the present study that early diagnosis of hypertension during neonatal period will help to control childhood hypertension and prevent future morbidity and mortality. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(2):106-111.